2011
DOI: 10.1111/j.1751-9020.2011.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐Solving Courts: Theory and Practice

Abstract: Problem-solving courts (PSCs) are a popular and fast-growing alternative to the usual way of handling criminal cases. In place of the adversarial process, they provide court-supervised treatment to certain groups of offenders by addressing the underlying causes of criminal behavior. They take on a variety of forms including drug courts, mental health courts, domestic violence courts, veterans' courts, and homeless courts. PSCs, as relatively new innovations in the criminal justice system, are still evolving in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Taken together, the specialty court and therapeutic jurisprudence literature paint a broad picture of how VTCs, as well as MHCs and DTCs, are different from traditional courts (Castellano, 2011;Drug Court Programs Office, Office of Justice Programs, 1997;Russell, 2009;Wexler & Winick, 1996;Winick, 2003). The general point is that specialty courts, like the VTC, often take a therapeutic approach instead of a solely punitive approach.…”
Section: Context Of Therapeutic Jurisprudencementioning
confidence: 96%
See 1 more Smart Citation
“…Taken together, the specialty court and therapeutic jurisprudence literature paint a broad picture of how VTCs, as well as MHCs and DTCs, are different from traditional courts (Castellano, 2011;Drug Court Programs Office, Office of Justice Programs, 1997;Russell, 2009;Wexler & Winick, 1996;Winick, 2003). The general point is that specialty courts, like the VTC, often take a therapeutic approach instead of a solely punitive approach.…”
Section: Context Of Therapeutic Jurisprudencementioning
confidence: 96%
“…Another important consideration drawn from this philosophy is that an offender's perception of fairness and transparency in the decision-making process may influence success in specialty courts (Frazer, 2007). For the purposes of this study, the key contribution of therapeutic jurisprudence to specialty court philosophy is that court officials view offender's problems from a broader point of view-these actors rely on treatment and resources as opposed to punishment to induce desistance (Castellano, 2011). Furthermore, this process unfolds in a collaborative, rather than an adversarial manner.…”
Section: Context Of Therapeutic Jurisprudencementioning
confidence: 97%
“…Problem‐solving courts, also called specialty courts, are an alternative to traditional criminal court processing. These courts divert offenders out of the criminal justice system and link them with treatment, services, and other community alternatives designed to alter the underlying problems associated with their criminal behavior (Miller and Johnson ; Porter, Rempel, and Mansky ; Castellano 2011a). Rather than emphasizing punishment, problem‐solving courts focus on ways to reduce future criminal offending by using the authority of the court to hold an offender accountable for actions while also offering incentives that encourage positive changes in the offender's life.…”
Section: Introductionmentioning
confidence: 99%
“…Future research is needed to explore whether such a model can assist MHCs in ensuring that their clients do not recidivate and are connected to appropriate treatment services. Castellano (2011a) recently observed that MHCs may be operating under a model of problem-solving jurisprudence. Essentially, problemsolving jurisprudence focuses on helping individuals in alternative court settings that are better able to address both personal and community problems.…”
Section: Does a Theoretical Basis Exist For How Mhcs Work?mentioning
confidence: 99%
“…MHC participants are typically referred by defense or prosecuting attorneys, judges, law enforcement professionals, (Castellano, 2011a) and in some cases family members. Wolff, Fabrikant, and Belenko analyzed six MHCs to determine how clients were identified, screened, recruited, excluded, and included for participation in their respective court programs.…”
Section: Selection Processmentioning
confidence: 99%